Leveraging green human resource management for sustainable tourism and hospitality: a mediation model for enhancing green reputation - Bassam Samir Al-Romeedy; Thaib Alharethi (Discover Sustainability)
Abstract This study examines the critical role of green entrepreneurial orientation (GEO), green innovation (GI), and green organizational identity (GOI) in mediating the relationship between green human resource management (GHRM) and green reputation (GR) through the lens of institutional theory. These elements are significant as they underscore how organizations can strategically enhance their green reputation, a critical factor for sustainability-focused industries like tourism and hospitality. Data was collected from employees of travel agencies in Saudi Arabia, and a Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis of 866 valid responses was performed. The findings reveal that GHRM directly and positively influences green reputation, while GEO, GI, and GOI serve as partial mediators, amplifying these effects. This study provides practical insights for industry professionals by highlighting actionable pathways to leverage GHRM practices for strengthening green reputation. The research underscores the strategic importance of embedding green initiatives into organizational practices to align with evolving sustainability goals and industry standards, offering new perspectives and implications for both academia and practitioners.